Effect of Sulfamerazine on Oxidative Stress of Rainbow Trout (Oncorhynchus mykiss, Walbaum, 1792) - Yonar, M. Enis; Yılmaz, Seval; Saglam, Naim (Durmuş Ali ARSLAN, 2023)
The aim of this study was to investigate effects of sulfamerazine on oxidative stress of rainbow trout (Oncorhynchus mykiss). The fish were divided into four groups. The first group was fed with diets containing no sulfamerazine; the second group was supplemented with sulfamerazine at 100 mg kg-1 for 21 days; the third group was treated with sulfamerazine at 200 mg kg-1 for 21 days; fourth group were supplemented with sulfamerazine at 400 kg-1 for 21days. Blood samples were taken to determine of the malondialdehyde (MDA) levels and catalase (CAT) activities from fish on the 3rd, 7th, 14th and 21st days of feeding. The levels of MDA were lower in the groups exposed to three different doses of sulfamerazine treatment than in the control group on day 3rd. MDA levels began to increase depending on time at group supplemented with sulfamerazine. MDA levels were found to be higher at fish exposed to 200 mg kg-1 dose than those observed in fish exposed to 100 and 400 mg kg-1 dose of sulfamerazine (P

Bu çalışmanın amacı gökkuşağı alabalığı (Oncorhynchus mykiss)' nda oksidatif stress üzerine sulsamerazinin etkilerini araştırmaktı. Balıklar dört gruba ayrıldı. İlk grup sulfamerazin içermeyen yemle (kontrol), ikinci grup 21 gün süreyle 100 mg kg-1, üçüncü grup 21 gün süreyle 200 mg kg-1, dördüncü grup 21 gün süreyle 400 mg kg-1 sulfamerazin içeren yemlerle beslendi. Balıklardan kan örnekleri beslemenin 3., 7., 14. ve 21. günlerinde malondialdehit (MDA) ve katalaz (CAT) aktivitelerini belirlemek için alındı. MDA düzeyleri, 3. günde sulfamerazinin üç farklı dozunun uygulandığı balıklarda kontrol grubundan daha düşüktü. MDA düzeyleri sulfamerazinle beslenen gruplarda zamana bağlı olarak artmaya başladı. 200 mg kg-1 dozunda sulfamerazin uygulanan balıkların MDA düzeyleri 100 ve 400 mg kg-1 oranında sulfamerazin uygulanan balıklara göre daha yüksek bulundu (P
Gökkuşağı Alabalığı (Oncorhynchus mykiss)'nda Oksidatif Stres Üzerine Sulfamerazinin Etkisi
Keywords: Agricultural; Veterinary and Food Sciences; Ziraat; Veterinerlik ve Gıda Bilimleri